Efek Pemberian Ekstrak Etanol Buah Adas (Foenicullum vulgare Mill.) terhadap Kadar Hormon Prolaktin Tikus Putih Betina Post Partum - Ahwan Abdul; Fridah Wahyu Safitri; Rantika Purbowati (Universitas Muhammadiyah Surakarta, 2020)
Fennel plants are plants that have various traditional properties, such as facilitating breast milk or lactagogum. The aim of this research was to give ethanol extract of fennel fruit to increase the level of the hormone prolactin in lactating mice, so that the milk produced was increased. Subjects consisted of 12 postpartum female rats, divided into 1 control group (1% CMC Na) and 3 treatment groups (doses of 100, 500 and 1000 mg / Kg BW). Fennel fruit extract was given orally for each group for 14 days, after the treatment of blood samples were taken and centrifuged, the serum was read by Elisa Reader. The data obtained were analyzed using the Kolmogorov-Smirnov test, one-way ANAVA and Tukey's Multiple Comparison (post hoc test). Fennel fruit extract given from a dose of 100; 500 and 1000 mg / kg BW can significantly increase levels of the hormone prolactin (p 0.05) in nursing mice, respectively by 42.11; 44.26 and 43.83 ng / mL compared to controls (32.64 ng/mL).